Advances in Ocular Drug Delivery System for Glaucoma Management – A Comprehensive Review - Raju Maski; Jitendra Banweer; Megha Mishra; Praveen Tahilani; Gaurav Goyanar (Indian Journal of Pharmacy & Drug Studies, 2023)
In today’s world delivery of ophthalmic drugs remains challenging despite easy accessibility via the ocular surface. Eye dropsare easy and most widely used for drug delivery for treating ocular infections, particularly involving the internal segmenthaving an additional benefit of avoiding first-pass metabolism there while passing through the systemic circulation. Thechallenges of drug administration through traditional methods involve improper patient education for drug installationtechniques, compliance, adherence, and persistence. Different dynamic and static ocular barriers involved only permit limiteddrug delivery to the target ocular tissues. In this review, we described the development of well-tolerated drug delivery systemsthat helps to overcome the factors limiting adequate drug delivery to the glaucomatous patients targeting infected tissues withtraditional techniques.